2011
DOI: 10.1186/1476-4598-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of NIMA-related kinase 1 (NEK1) leads to chromosome instability

Abstract: BackgroundNEK1, the first mammalian ortholog of the fungal protein kinase never-in-mitosis A (NIMA), is involved early in the DNA damage sensing/repair pathway. A defect in DNA repair in NEK1-deficient cells is suggested by persistence of DNA double strand breaks after low dose ionizing radiation (IR). NEK1-deficient cells also fail to activate the checkpoint kinases CHK1 and CHK2, and fail to arrest properly at G1/S or G2/M-phase checkpoints after DNA damage.ResultsWe show here that NEK1-deficient cells suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 40 publications
1
57
1
Order By: Relevance
“…Nek1 −/− mutant mice displayed several phenotypes similar to those of the hypomorphic ATR-Seckel mutant mice, such as dwarfism, sterility, and anemia (37). Similar to some Seckel patients, Nek +/− mutant mice developed lymphoma (38,39). Interestingly, loss of Nek1 has been linked to defective ciliogenesis and progressive kidney failure in both mouse and human (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 97%
“…Nek1 −/− mutant mice displayed several phenotypes similar to those of the hypomorphic ATR-Seckel mutant mice, such as dwarfism, sterility, and anemia (37). Similar to some Seckel patients, Nek +/− mutant mice developed lymphoma (38,39). Interestingly, loss of Nek1 has been linked to defective ciliogenesis and progressive kidney failure in both mouse and human (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 97%
“…Its protein product is a dual serine-threonine and tyrosine kinase required for efficient DNA damage checkpoint activation and for maintaining chromosome stability. 42 Moreover, there is evidence to suggest that NEK1 functions as a tumor suppressor. 42 In the present study, 2 of 93 high-risk PC families were found to carry a novel NEK1 :p.Ala563Tyrfs*36 variant.…”
Section: Discussionmentioning
confidence: 99%
“…47 The functional and pathological roles of these newly discovered genetic alterations in the context of cHL are yet to be determined; this is challenging because of the lack of cHL animal models or cell culture systems that include the tumor cell microenvironment. The role of B2M in cHL pathogenesis deserves particular mention.…”
Section: Discussionmentioning
confidence: 99%